Exploring learning and behavior problems of gifted children in Indonesia: A content analysis study - Pujaningsih Pujaningsih; Mar’atu Husnia Alfi (Jurnal Prima Edukasia, 2022)
Although gifted children have talents and positive traits in academic area that already been supported, little empirical evidence addresses the need of support for gifted children in non-academic areas in Indonesian context.  To fill this void, this study conducted a content analysis of two books about gifted children based on parents’ narratives to explore the need for support for social-emotional problems. “Menyongsong Pagi” and “Menyiangi Petang” are the two books which describe how thirteen gifted children grew up and face obstacle in their learning. Drawing on the theory of positive disintegration and Bronfenbrenner’s theory of ecological development, this study analyzed the two books to describe the uniqueness of gifted students in terms of emotion, intellectual and psychomotor still mostly seen as problems by their teachers and friends which lead to various educational issues. The implication of this study calls for the comprehensive support from teachers and schools’ leader to support gifted children both in academic and non-academic areas.